GFP-based evaluation system of recombinant expression through the secretory pathway in insect cells and its application to the extracellular domains of class C GPCRs - Ashikawa, Yuji (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Applications of the GFP-fusion technique have greatly facilitated evaluations of the amounts and qualities of sample proteins used for structural analyses. In this study, we applied the GFP-based sample evaluation to secreted protein expression by insect cells. We verified that a GFP variant, GFPuv, retains proper folding and monodispersity within all expression spaces in Sf9 cells, such as the cytosol, organelles, and even the extracellular space after secretion, and thus can serve as a proper folding reporter for recombinant proteins. We then applied the GFPuv-based system to the extracellular domains of class C G-protein coupled receptors (GPCRs) and examined their localization, folding, and oligomerization upon insect cell expression. The extracellular domain of metabotropic glutamate receptor 1 (mGluR1) exhibited good secreted expression by Sf9 cells, and the secreted proteins formed dimer with a monodisperse hydrodynamic state favorable for crystallization, consistent with the results from previous successful structural analyses. In contrast, the extracellular domains of sweet/umami taste receptors (T1R) almost completely remained in the cell. Notably, the T1R and mGluR1 subfractions that remained in the cellular space showed polydisperse hydrodynamic states with large aggregated fractions, without forming dimers. These results indicated that the proper folding and oligomerization of the extracellular domains of the class C GPCR are achieved through the secretory pathway.